A visual exploration into the natural and urban landscapes of Colorado - Gibbons, Jenna, author (Colorado State University. Libraries, 2024)
This honors thesis aims to educate individuals on the Colorado landscape through the unique, personal lens of a landscape architect. Additionally, this honors thesis intends to be a personal archive and portfolio piece. The project includes explanations and examples of key landscape architecture terms such as landscape, natural landscapes, and urban landscapes, as well as an investigation into three case studies of urban and natural Colorado landscapes. The photo archive at the end serves as a reference as well as a personal portfolio.
University Honors Program.